Principals’ Leadership Strategies for Improving the Quality of Education in Vocational High Schools - Musa Azzam Al Asy'Ari; Triono Ali Mustofa (Jurnal Inovasi Pendidikan dan Sains, 2025)
This study aims to analyze the leadership strategies of the principal in improving the quality of education at SMK Muhammadiyah 2 Andong Boyolali. A qualitative approach with a field study method was used to analyze the implementation of participatory and contextual leadership in the context of an Islamic-based vocational high school in a rural area. The research data were obtained through participatory observation, interviews, and document studies, and the Miles and Huberman model was used to analyze this research. The results of the study showed that the principal implemented quality improvement strategies systematically through the formulation of shared vision and mission, SWOT analysis, short-term to long-term planning, as well as the development of flagship programs based on local needs. The implementation of these strategies was supported by the establishment of internal policies, human resource empowerment, and the enhancement of teacher motivation. The evaluation of the strategies was carried out periodically to maintain their relevance and effectiveness. These findings affirm that collaborative leadership that adapts to the local context is capable of creating a sustainable culture of educational quality in rural vocational schools. This study provides a theoretical contribution to the development of an educational leadership model that is relevant to the Indonesian context